The Effects of Large-Scale Social Movements on Language Attitudes: Cantonese and Mandarin in Hong Kong. (June 2023) - Shum, Priscilla Lok-chee; Tse, Chi-Shing; Hamamura, Takeshi; Wright, Stephen C.
Speakers with standard accents are typically judged more favorably than non-standard speakers, but this may shift in response to perceived intergroup conflict with ethnolinguistic outgroups. Three studies were conducted to examine how large-scale social movements may impact language attitudes in Hong Kong. Attitudes toward standard-accented and non-standard-accented Cantonese and Mandarin were collected across four instances in 2013 and 2015 (pre- and post-Umbrella Movement), 2018 and 2019 (pre- and post-Anti-Extradition Bill Movement), respectively. Compared to Study 1 (2013), Hong Kong participants judged standard speakers of Cantonese (the ingroup variety), and ingroup, non-standard speakers of Mandarin (the outgroup variety) significantly more favorably in Study 2 (2015). Study 3 showed that the retrospective endorsement of the Umbrella Movement moderated preferences for standard Cantonese and Mandarin speakers. Comparison of 2018 and 2019 data partially replicated the findings in Studies 1 and 2, though the current endorsement of the Anti-Extradition Bill Movement did not moderate preferences for standard speakers.